Sexed semen technology for cattle breeding: an interpretative review on its performance, and implications for India’s dairy economy - Amit Thakur; Pratap S Birthal (Agricultural Economics Research Review, 2023)
Sexed semen is an innovative biotechnological tool for improving the production efficiency, reproductive performance and economics of dairy farms. Despite these benefits, the adoption of sex semen is limited to the commercial dairy herds. Several factors such as its low conception rate and high cost restrict its applicability in smallholder dairy production systems. Further improvement in the technology can narrow don the fertility gaps between the sexed semen and conventional AI, leading to an improvements in adoption and profitability. Rising demand for milk and declining utility of male cattle in India reinforces the need for the adoption of sexed semen technology.